Albumin nanocomposites with MnO2/Gd2O3 motifs for precise MR imaging of acute myocardial infarction in rabbit models. (February 2020) - Wang, Fang; Wen, Linyi; Liu, Jing; Peng, Wanlin; Meng, Zihan; Chen, Qixian; Wang, Yao; Ke, Bowen; Guo, Yingkun; Mi, Peng
Abstract: The severe mortality and morbidity of myocardial infarction requests appropriate and accurate detection. Considering pathological profile of the acidic myocardial infarction microenvironments, herein, the low pH-sensitive albumin nanocomposites with MnO2 motifs (MnO2 @BSA) have been engineered for T 1 -weighted MR imaging of myocardial infarction, while using non-pH-responsive Gd2 O3 @BSA nanocomposites as control. The nanocomposites were 20–30 nm in diameter with spheroid morphology. Besides, the MnO2 @BSA have exhibited pH-triggered releasing of Mn 2+, demonstrating approximately 38-fold and 55-fold increased molecular relaxivity at acute myocardial infarction-mimicking pH 6.5 (13.08 mM −1 s −1 ) and macrophage intracellular pH 5.0 (18.76 mM −1 s −1 ) compared to the extremely low relaxivity (0.34 mM −1 s −1 ) at normal physiological conditions (pH 7.4). However, the Gd2 O3 @BSA with molecular relaxivity approximately 10 mM −1 s −1 were without pH-sensitive properties. Furthermore, the MnO2 @BSA have demonstrated high accumulation in the acute myocardial infarction regions and fast metabolism from the body after systemic injection, accounting high contrast enhancement for accurate MR imaging of acute myocardial infarction in rabbit models, demonstrating better diagnostic performance over the controls.